On Mixed Type Duality for Multiobjective Programming Containing Support Functions (Journal of Informatics and Mathematical Sciences, 2010)
A mixed type vector dual to a multiobjective programming problem containing support functions is formulated and various duality results are proved under generalized invexity conditions. Special cases are generated from our results.
Keywords: Multiobjective programming problem; Support functions; Mixed type duality; Generalized invexity; Related problems